The concept of self in modern and contemporary philosophy - Farha, Mohammad; Ali , Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research tries to examine the concept of self within the framework of modern philosophy and contemporary philosophy, in an attempt to highlight the role of this concept in the formation of most of the philosophical doctrines from the Greek era to the contemporary philosophy, through modern philosophy. In this research, we will attempt to study the formation of this concept in the framework of modern and contemporary philosophy, to show the philosophers' interest in this concept and the extent to which the concept is linked to the clarify their own philosophy. Therefore, the research attempts to provide a follow-up reading of the concept of self in a comparative historical context, in which we demonstrate that this concept is still alive in contemporary philosophy, albeit with different names, such as reason, mind or feeling. We will conclude from this the importance of the concept of self in the philosophical context, which still occupies an important space in the thinking of modern and contemporary philosophers. Here we will try to ask several questions, including what is the dualism of the soul and body. How can the soul be a logical synthesis, an emanated mind, or a subjective feeling? In this research, we will try to answer these questions and other questions that will appear in the context of the research.